Presentation of electrical control results by electrophysical chromatography method - V. I. Surin; A. S. Shcherban; A. A. Shcherbakov; M. B. Ivanyi; M. E. Zhidkov; S. A. Tomilin; A. V. Kozlov (Глобальная ядерная безопасность, 2023)
A method of electrophysical chromatography was proposed to visualize the results of electrical non-destructive testing for the first time. Surface potentiograms usually used to represent the results of scanning contact potentiometry are replaced by volumetric images of structural inhomogeneities. The alternative has obvious advantages as useful additional information can drastically change the results of testing which is demonstrated by the example of a weld overlay. Methodological recommendations for constructing volumetric images of defects are formulated and implemented. The causes of self-shielding of structural inhomogeneities at different levels of fixation which are due to the mutual spatial overlap of microregions emitting waves of elastic stresses are discussed. The biggest problems in identifying defects for NDT are their complete or partial screening. The electrophysical chromatography method requires at least one experimental array obtained from the following measurements: double scanning of the surfaces of the test object; double simultaneous scanning of the surfaces of the test object; double simultaneous scanning of the surfaces of the test object using a radiation synchronizer in time or frequency. In the case of scanning along one (external or internal) surface, the coordinates of defects are determined from the corresponding cross sections and the calculated values of their depth using frequency and time-frequency analysis